Principles of genetics - Tamarin, Robert H. (WCB/McGraw-Hill, 1999)
Snustad provides scientists with the confidence to apply problem solving to the major principals of genetics. It eases them into the art of problem solving by integrating problems within each chapter. A clear connection between key principals and related problems is presented in each chapter. Icons help them clearly see how a problem is worked out before reading on. The fifth edition has also been revised with an improved art program. It offers more balanced coverage of traditional and modern topics by weaving classical genetics with molecular genetics, and illustrating the connection between the two. The book is problem-solving-centric as well. Chapters now contain problems that correlate with major principals. Coverage of both classic experiments and current research will allow scientists to gain perspective on the process of science.